2020
DOI: 10.3390/ijerph17061876
|View full text |Cite
|
Sign up to set email alerts
|

Footprint Curvature in Spanish Women: Implications for Footwear Fit

Abstract: The incorrect adjustment of footwear produces alterations in the foot that affect quality of life. The usual measurements for shoe design are lengths, widths and girths, but these measures are insufficient. The foot presents an angle between the forefoot and the rearfoot in the transverse plane, which is associated with foot pronation, hallux valgus and metatarsus adductus. Here, we aimed at identifying the groups formed by the angulations between the forefoot and rearfoot using a sample of footprints from 102… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Moreover, in several studies, use of unstable shoes not only showed benefits for balance, but also showed benefits with regard to enhancement of shock absorption of ground reaction forces. 25,28,29 The current study suggested that use of unstable shoes had benefits regarding pain intensity and improvement of COP imbalances, while being a relatively inexpensive and portable intervention.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, in several studies, use of unstable shoes not only showed benefits for balance, but also showed benefits with regard to enhancement of shock absorption of ground reaction forces. 25,28,29 The current study suggested that use of unstable shoes had benefits regarding pain intensity and improvement of COP imbalances, while being a relatively inexpensive and portable intervention.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, in several studies, use of unstable shoes not only showed benefits for balance, but also showed benefits with regard to enhancement of shock absorption of ground reaction forces. 25 , 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of mechanics and materials science, sports footwear should be capable of reducing impact forces exerted on the lower extremity [1]. Previous studies have reported that wearing different shoelace patterns shows different peak loading rates [9]; meanwhile the use of shoes with an incorrect length can cause foot injuries [10]. Moreover, it was reported that wearing cushioned shoes could reduce ground reaction forces (GRFs) [11] and vertical loading rates (LRs) [12], which have been hypothesised to reduce running-related injury risks, such as stress fractures [13].…”
Section: Introductionmentioning
confidence: 99%